PENGARUH METODE RESITASI TERHADAP PRESTASI HASIL BELAJAR PENDIDIKAN ASWAJA NAHDLATUL ULAMA - Denissaputra; Ahmad Ma'ruf (Mu'allim, 2020)
This thesis discusses the influence of the method ofrecitation of education learning outcomes Aswaja Nahdlatul Ulamaclass IV Madrasah Diniyah Ketuwon Sumberrejo. This study wasbacked by the problems in the process of teaching and learningactivities, how to send the material to learners optimally and effectivelyso as to create an interactive educative between educators andlearners. The lack of interest of teachers in the variation of use ofteaching methods makes learners feel saturated in the process oflearning to teach, the result of quality improvement efforts is notrunning optimally and effectively. This research is experimental ASNexperiments. This research aims to determine the influence of themethod of recitation on the achievement of education OutcomesAswaja Nahdlatul Ulama class IV Madrasah Diniyah Shobibur RohmatKetuwon Sumberrejo. This research uses a quantitative approach withthe type of experiment. Variables in this study are free variables in theform of students of grade IV Madrasah Diniyah Shobibur Rohmat andthe variables are tied in the form of student learning outcomes, thesubject of this study is all students of grade IV Madrasah DiniyahShobibur Rohmat amounted to 19 students and samples in the studytook all class IV students Madrasah Diniyah Shobibur Rohmat whichamounted to The technique of data collection in this research is thedouble choice test in the form of pretests and posttest. Testing ofhypotheses requirements using test (Independent Sample T-Test).The results are known that there is a difference between the results oflearning using the method of resitation with conventional methods, thevalue of studying students using conventional methods of 63.42 andafter using the method of Resitation of 76.05. Differences in learningoutcomes use a resitation method of 19%. The inconclusive methodof resitation can affect the achievement of student learning outcomes,analysis of student test results in tests using t test with the acquisitionof T 8.715.